2007
DOI: 10.1016/j.jasms.2007.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Factors that impact the vacuum ultraviolet photofragmentation of peptide ions

Abstract: Several groups have investigated the photodissociation of peptide ions with ultraviolet light. Significant differences have been reported with 157 and 193 nm excitation. Recent studies have shown that the mass analyzer can also influence the observed photofragment distribution.Comparison of experiments using different peptides, wavelengths, and mass analyzers is undesirably complicated. In the present work, several peptides are analyzed with both 157 and 193 nm photodissociation in tandem-TOF and linear ion tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(107 citation statements)
references
References 29 publications
5
102
0
Order By: Relevance
“…Melittin, kassinin, Lys [0]bradykinin, bradykinin, dynorphin-␤, GSK-␤ ␤ inhibitor, myosin kinase inhibitor, and mouse ANP [1][2][3][4][5][6][7][8][9][10][11] were purchased from American Peptide Company (Sunnyvale, CA). Polyalanine peptides were synthesized in-house using standard Fmoc coupling methodology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melittin, kassinin, Lys [0]bradykinin, bradykinin, dynorphin-␤, GSK-␤ ␤ inhibitor, myosin kinase inhibitor, and mouse ANP [1][2][3][4][5][6][7][8][9][10][11] were purchased from American Peptide Company (Sunnyvale, CA). Polyalanine peptides were synthesized in-house using standard Fmoc coupling methodology.…”
Section: Methodsmentioning
confidence: 99%
“…It is demonstrated that a naphthyl based 18-crown-6 adduct is ideally suited for attaching to a variety peptides and fragmenting them following absorption of 266 nm light. [7][8][9][10][11]. Though none of these techniques is perfect, each has characteristic strengths and weaknesses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To combat these issues, significant interest has been placed in the development of new ion activation methods, such as electronic excitation dissociation (EED) [16], electron ionization dissociation (EID) [17], ultraviolet photodissociation (UVPD) [18,19], femtosecond laser-induced ionization/ dissociation (fs-LID) [20], action spectroscopy (synchrotron radiation) [21], and metastable atom-activated dissociation (MAD) [22,23]. These fragmentation methods all possess a common feature-the capability of dissociating low charge state (1+ & 2+) precursor ions, thus providing complementary structural information to ETD/ECD.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the common ion/ion dissociation methods, CTD utilizes the interaction between homo-polarity ions such as peptide cations and helium cations, which, in the case of 1+ substance P, results in a dominant series of a ions. It has been widely reported that the fragmentation pattern of MS/MS techniques shows certain dependence on the charge state of precursor ions and the type of mass analyzer [14,19,25]. To investigate this dependence, CTD fragmentation of substance P and bradykinin at different charge states (1+, 2+, and 3+) was carried out in a 3D ion trap mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%